Measure of Rotatability for a Class of Balanced Ternary Design - Rajyalakshmi, K.; Varalakshmi, M. (Communications in Mathematics and Applications, 2022)
In the present study we mainly focused on a measure of rotatability for a class of Balanced ternary designs. It is very much useful to assess the degree of a rotatability for a given response surface design.
Keywords: Response surface designs; Second order rotatable designs; Measure of rotatability